2022
DOI: 10.3233/shti220886
|View full text |Cite
|
Sign up to set email alerts
|

The Future of eXtended Reality in Primary and Secondary Education

Abstract: eXtended Reality (XR) technology has to some degree been used in primary and secondary education. However, XR technology has not gained widespread use in public schools due to challenges related to pedagogical content, expertise, digital infrastructure, funding, and a lack of universal design. In this paper, we present the results from focus group interviews with representative stakeholders from the private and public sectors, in which we investigated their practical experiences and opinions about XR technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…There are numerous opportunities for use of XR technology in primary and secondary education. General pedagogical opportunities have been reviewed elsewhere [13]: XR is first and foremost technology for mediating experiential learning. XR can bring abstract topics into a more practical learning context.…”
Section: Opportunitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…There are numerous opportunities for use of XR technology in primary and secondary education. General pedagogical opportunities have been reviewed elsewhere [13]: XR is first and foremost technology for mediating experiential learning. XR can bring abstract topics into a more practical learning context.…”
Section: Opportunitiesmentioning
confidence: 99%
“…Moreover, we reviewed common barriers for people with cognitive, sensory, and physical disabilities [14]. General opportunities in the classroom and systemic challenges of XR technology have been reviewed elsewhere [13].…”
Section: Comparison Between the Literature And The Interviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, XR educational software usability is another challenge that has been highlighted in the literature alongside the cost of XR [33]. Therefore, despite years of XR technologies being introduced in education, they have not gained widespread use in schools due to challenges related to pedagogical content, expertise, digital infrastructure, funding, and a lack of universal design [34].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although several studies have reported positive aspects of the integration of XR in schools, the widespread integration of XR as an educational resource for the improvement of the teaching-learning process is hampered by various barriers that limit its effective implementation [6]. This research has transformative potential in education, allowing students to have access to sensory experiences that improve the retention of the knowledge imparted.…”
Section: Introductionmentioning
confidence: 99%